Knowledge of general medicine students from the medical faculties in Tuzla and Zenica about lung cancer prevention - Amar Terzimehić; Elma Kuduzović; Nino Hasanica; Muhamed Skomorac; Erna Terzić; Iman Kovač (Medicinski glasnik, 2026)
Aim: To assess the level of knowledge about risk factors and prevention of lung cancer among medical students, and to identify differences in knowledge based on the year of study and previous secondary education background. Methods: The study was conducted among 223 students of the School of Medicine, University of Zenica, and the School of Medicine, University Clinical Center Tuzla using an anonymous online survey via the Google Forms platform. The collected data were analyzed using descriptive statistics and the χ2 test to assess statistical significance. Results: The majority of students identified smoking as the main risk factor for lung cancer, while air pollution was rated as the most overlooked risk factor. There were significant differences in the perception of neglected risk factors between years of study (p<0.05). Most students from Zenica acquire their knowledge through formal education, while students from Tuzla more often rely on the internet and media (p<0.05). Additionally, 82.5% of students believe that passive smoking is equally harmful as active smoking, with no significant differences between groups. Conclusion: Medical students demonstrate a good level of awareness regarding risk factors and prevention of lung cancer; however, there is a need for greater emphasis on environmental risks and passive smoking in their education. The results highlight the importance of continuous education to ensure that future healthcare professionals are equipped to effectively promote health and prevent this disease.
Keywords: air pollution; health knowledge attitudes practice; lung neoplasms / prevention & amp; amp; control; medical students; smoking